Endemism and functional convergence across the North American soil mycobiome - Talbot, Jennifer M.; Bruns, Thomas D.; Taylor, John W.; Smith, Dylan P.; Branco, Sara; Glassman, Sydney I.; Erlandson, Sonya; Vilgalys, Rytas; Liao, Hui-Ling; Smith, Matthew E.; Peay, Kabir G. (Proceedings of the National Academy of Sciences - PNAS, 2014)
Identifying the ecological processes that structure communities and the consequences for ecosystem function is a central goal of ecology. The recognition that fungi, bacteria, and viruses control key ecosystem functions has made microbial communities a major focus of this field. Because many ecological processes are apparent only at particular spatial or temporal scales, a complete understanding of the linkages between microbial community, environment, and function requires analysis across a wide range of scales. Here, we map the biological and functional geography of soil fungi from local to continental scales and show that the principal ecological processes controlling community structure and function operate at different scales. Similar to plants or animals, most soil fungi are endemic to particular bioregions, suggesting that factors operating at large spatial scales, like dispersal limitation or climate, are the first-order determinants of fungal community structure in nature. By contrast, soil extracellular enzyme activity is highly convergent across bioregions and widely differing fungal communities. Instead, soil enzyme activity is correlated with local soil environment and distribution of fungal traits within the community. The lack of structure–function relationships for soil fungal communities at continental scales indicates a high degree of functional redundancy among fungal communities in global biogeochemical cycles.